Optimization-based analysis of decarbonization pathways and flexibility requirements in highly renewable power systems. (1st November 2021) - Verástegui, Felipe; Lorca, Álvaro; Olivares, Daniel; Negrete-Pincetic, Matias
Abstract: Several countries are adopting plans to reduce the contaminant emissions from the energy sector through renewable energy integration and restrictions on fossil fuel generation. This process poses important computational and methodological challenges on expansion planning modeling due to the operational details needed for a proper analysis. In this context, this paper develops a planning model including an effective representation of the operational aspects of the system to understand the key role of flexible resources under strong decarbonization processes in highly renewable power systems. A case study is developed for the Chilean power system, which is currently undergoing an ambitious coal phase-out process, including the analysis of a scenario that leads to a completely renewable generation mix. The results show that highly renewable generation mixes are feasible, but rely on an effective balance of the key flexibility attributes of the system including ramping, storage, and transmission capacities. Further, such balance allows for faster decarbonization goals to remain in a similar cost range, through the deployment of flexible capacity in earlier stages of the planning horizon. Highlights: Flexibility is a critical challenge for the decarbonization of power systems. Planning models with operational detail capture key trends through decarbonization. A planning model with a linear relaxation of the unit commitment problem is proposed. A case study on decarbonization pathways for the Chilean power system is presented. Fully renewable mixes are feasible through a proper balance of flexibility attributes.